Rethinking the contemporary art school: The artist, the PhD and the academy - Buckley, Brad; Conomos, John (Halifax Nova Scotia The Press of the Nova Scotia College of Art and Design, 2009)
With great timeliness, Rethinking the Contemporary Art School examines the very basis of the art school and its role in society. The book considers various art-school models-innovative graduate programs, independent stand-alone schools and art schools that are departments or schools of major research universities-and the problems that art schools face as academically marginalized institutions. Rethinking the Contemporary Art School concludes with essays on new media, inquiring whether the contemporary art school offers the right context for this discipline. The anthology includes contributions by Su Baker, Bruce Barber, Mikkel Bogh, Juli Carson and Bruce Yonemoto, Edward Colless, Jay Coogan, Luc Courchesne, Sara Diamond, Lauren Ewing, Gary Pearson, Bill Seaman and Jeremy Welsh.